Novel temporin L antimicrobial peptides: promoting self-assembling by lipidic tags to tackle superbugs - Bellavita, Rosa (J Enzyme Inhib Med Chem, 2020)
The rapid development of antimicrobial resistance is pushing the search in the discovering of novel antimicrobial molecules to prevent and treat bacterial infections. Self-assembling antimicrobial peptides, as the lipidated peptides, are a novel and promising class of molecules capable of meeting this need. Based on previous work on Temporin L analogs, several new molecules lipidated at the N- or and the C-terminus were synthesised. Our goal is to improve membrane interactions through finely tuning self-assembly to reduce oligomerisation in aqueous solution and enhance self-assembly in bacterial membranes while reducing toxicity against human cells. The results here reported show that the length of the aliphatic moiety is a key factor to control target cell specificity and the oligomeric state of peptides either in aqueous solution or in a membrane-mimicking environment. The results of this study pave the way for the design of novel molecules with enhanced activities.